2022
DOI: 10.1002/jcla.24644
|View full text |Cite
|
Sign up to set email alerts
|

A peptide translated from circPPP1R12A promotes the malignancy of non‐small cell lung cancer cells through AKT signaling pathway

Abstract: Background Recent literature have indicated that the malignancy of cancer cells is modulated by hsa_circ_0000423 (named circPPP1R12A) through the way of translating protein. Herein, we investigated the role and latent mechanisms of circPPP1R12A in Non‐Small Cell Lung Cancer (NSCLC). Methods CircPPP1R12A expression was measured by qRT‐PCR. The malignancy of NSCLC was determined by CCK‐8, TUNEL assay, Wound healing, Transwell and Western blotting assays. The underlying mechanisms of circPPP1R12A were confirmed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Subsequently, circPPP1R12A was shown to encode a newly identified protein, circPPP1R12A-73aa, which has been previously reported to play a catalytic role in colon cancer (61). Subsequently, Zhao et al (76) found that the expression of circPPP1R12A was also significantly increased in small-cell lung cancer, and its associated protein circPPP73R1A-73aa could promote the proliferation of small-cell lung cancer through the AKT pathway. Therefore, this study also provided useful insights and suggestions for the clinical treatment of NSCLC.…”
Section: Circrna-encoded Proteins and Gastric Cancer (Gc)mentioning
confidence: 99%
“…Subsequently, circPPP1R12A was shown to encode a newly identified protein, circPPP1R12A-73aa, which has been previously reported to play a catalytic role in colon cancer (61). Subsequently, Zhao et al (76) found that the expression of circPPP1R12A was also significantly increased in small-cell lung cancer, and its associated protein circPPP73R1A-73aa could promote the proliferation of small-cell lung cancer through the AKT pathway. Therefore, this study also provided useful insights and suggestions for the clinical treatment of NSCLC.…”
Section: Circrna-encoded Proteins and Gastric Cancer (Gc)mentioning
confidence: 99%